Gut Dysbiosis in Pancreatic Diseases: A Causative Factor and a Novel Therapeutic Target - Zhang, Tao; Gao, Guangqi; Sakandar, Hafiz Arbab; Kwok, Lai-Yu; Sun, Zhihong (Frontiers in Nutrition, 2022)
Pancreatic-related disorders such as pancreatitis, pancreatic cancer, and type 1 diabetes mellitus (T1DM) impose a substantial challenge to human health and wellbeing. Even though our understanding of the initiation and progression of pancreatic diseases has broadened over time, no effective therapeutics is yet available for these disorders. Mounting evidence suggests that gut dysbiosis is closely related to human health and disease, and pancreatic diseases are no exception. Now much effort is under way to explore the correlation and eventually potential causation between the gut microbiome and the course of pancreatic diseases, as well as to develop novel preventive and/or therapeutic strategies of targeted microbiome modulation by probiotics, prebiotics, synbiotics, postbiotics, and fecal microbiota transplantation (FMT) for these multifactorial disorders. Attempts to dissect the intestinal microbial landscape and its metabolic profile might enable deep insight into a holistic picture of these complex conditions. This article aims to review the subtle yet intimate nexus loop between the gut microbiome and pancreatic diseases, with a particular focus on current evidence supporting the feasibility of preventing and controlling pancreatic diseases via microbiome-based therapeutics and therapies.